ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR IPAS PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Ida Nur Aini; Zhafarina Harin Widyawati; Ana Maria Shofiana; Fiska Noviana Wulandari; Evia Raihanatun Nabilah; F. Shoufika Hilyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning difficulties in learning greatly influence students' abilities and learning outcomes at school. Learning difficulties experienced by students are definitely caused by factors that influence the occurrence of obstacles or disruptions in learning. This research aims to analyze and explain the factors that cause students' learning difficulties in science subjects in participating in learning implementation. Factors that cause students' learning difficulties can come from internal factors or external factors. The subjects in this research were fifth grade elementary school students. The method used in this research is literature study or literature review. The data collection methods used in this research were observation, interviews and questionnaires. Based on the research results obtained, the learning difficulties of fifth grade elementary school students are influenced by two factors, namely internal factors and external factors. Internal factors that influence students' learning difficulties are students' low interest in learning, students' lack of concentration, students' lack of activeness and enthusiasm for learning, and students' less than optimal abilities, where these factors come from within the students. Meanwhile, external factors that influence are a lack of attention and learning guidance from parents, inappropriate selection of methods and models and presentation of learning, as well as a lack of adequate learning media.